Sekolah Alam Melawan: Membangun Masyarakat Melawan Atas Kesadaran Berpendidikan - Hapsari, Hanisah; Nur Ramadhan, Rahmat Rizky; Wibawa, Andi Prasetya; Yarison, Aulisa Maulani; Latifah, Indah; Noor, Al Fikrian; Sofyaningsih, Eka; Rahmadhani, Amelia (LP2M UIN Sultan Aji Muhammad Idris Samarinda, 2023)
Education has a very important role in raising the degree and quality of life of marginalized communities or so-called marginal communities. Education as a breaker of the cycle of poverty that is often experienced by marginalized communities. By providing access to education, it can open opportunities for marginalized communities to gain an understanding of social life and improve the quality of life. Schools are one way to improve the quality of education in society. Alam Melawan School is an informal educational institution located in Melawan Village, Pinang Raya, South Sangatta Village. This school was founded as a form of humanity due to the lack of interest of parents in Kampung Melawan in sending their children to school outside the area for various reasons, such as difficulty accessing roads and an economy that is more than sufficient to fulfill them through their current work, namely farming and gardening. The purpose of establishing this school is to increase the level of education of the Melawan community so that awareness grows in education. The hope is that this program will make the Melawan people aware by sending their children outside, namely in formal schools for higher education. The service is carried out by actively participating in learning activities at the Alam Melawan School. As volunteers at the Melawan School, we obtained the result that the Alam Melawan School needed assistance to issue an official school operational permit so that it could become a formal, legal educational institution. So that you can get the help of proper infrastructure to be used in the learning process. With the existence of the Melawan Nature School, the Melawan community has begun to grow in awareness to enroll their children in this natural school.